A clinico pathological study of acute appendicitis with special reference to ultrasonography - Inamdar, Mohammed Faheem; Manjappa, Sali; Inamdar, N. M. (International Surgery Journal, 2017)
Background: Acute appendicitis is one of the commonest conditions treated at emergency, despite of advances in diagnostic medicine and therapeutics, the diagnosis of appendicitis remains essentially clinical, requiring clinical acumen and surgical knowledge. Maximum incidence noted in second and third decade of life with male predominance. Ultrasonograpy is shown to be effective in the diagnosis of acute appendicitis with a sensitivity of 84 to 89% and specificity of 92 to 98%. Objectives of the study was to study the clinical features of acute appendicitis regarding Alvarado score. Role of USG and HPE Examination in supporting the clinical diagnosis of acute appendicitis and the morbidity, mortality of emergency appendicectomy. Methods: 100 patients who were admitted to VIMS hospital, Bellary, from November 2004 to April 2006 with a clinical suspicion of acute appendicitis were included in the present study. Ultrasonography and Histopathological Examination was done in all cases and results were correlated with final analysis. Results were analyzed using ’Z’ test, Chi-squire test, sensitivity and specificity. Results: In present study of 100 cases 77 were males and 23 Females patient. Out of which 60 are in 15 to 30 years, 21 patients are 10 to 15 years followed by 13 in the age group of 30-40 years. All are undergone appendicectomy. 11 patents undergone Elective, and 89 emergency appendicectomy. Ultrasound was coming positive in 92 cases and negative in 8 cases. The sensitivity and specificity of 95.7% and 80% Respectively. HPE was done in all 100 cases 95 were positive 5 were negative with sensitivity of 96.8% and specificity of 80%. Conclusions: Appendicitis is commonest in 2nd and 3rd decade followed by 4th decade with a male preponderance, Ultrasonography is useful in females to rule out any gynecological pathology. Patients who come early within 2 to 3 days of symptoms of acute appendicitis, emergency appendicectomy is the treatment of the choice and were will be less morbidity and mortality, post operatively.